Building Trust in Telesurgery through Blockchain-Based Patient Consent and Surgeon Authentication - Ishiaku, Awwal; Maloletov, Alexander (Journal of Telecommunications and the Digital Economy, 2023)
Telesurgery, which enables remote surgical procedures, has the potential to revolutionize healthcare by improving access to specialized care and reducing costs. However, trust in telesurgery is a major concern for patients and healthcare providers. To address this issue, we propose a novel system for building trust in telesurgery through blockchain-based patient consent and surgeon authentication. Our system uses a smart contract on the blockchain to store patient consent and surgeon authentication data, which is securely verified by the telesurgery robot. We present a simulation of our system and evaluate its performance. Our results show that our system can authenticate surgeons and grant patient consent quickly and securely. This system has the potential to increase trust in telesurgery and promote its widespread adoption.